Intercorporeality: connectedness and creative collaboration in the embodied practice of dance - Purser, Aimie Christianne Elizabeth. (2016)
Dance plays a role in healing rituals across a number of cultures and is also recognised to promote social bonding. This, of course, includes contemporary Western medicine, in which dance is used in psychotherapeutic contexts in the form of dance/movement therapy (DMT). As a contribution to the burgeoning field of health humanities, this paper seeks to explore the power of dance to mitigate human suffering and reacquaint us with what it means to be human through bringing the embodied practice of dance into dialogue with the work of the French philosopher Maurice Merleau-Ponty. The promise of the health humanities is of a broader and richer understanding of what is healthful and therapeutic through exploration of and insight into the human condition. As such, it celebrates the uses of arts and humanities within traditional healthcare settings, practices and training, but also calls for a reimaging of the boundaries of health and healing, so that our intellectual and therapeutic focus might escape the physical and, perhaps more importantly, the epistemological constraints of the clinical. In this spirit, this paper presents an alternative understanding of dance as therapeutic, which is based in philosophy rather than in the psy-disciplines or the neuroscientific insights that currently dominate the literature of DMT as a clinical practice.